Questionnaires measuring patient participation in patient safety—A systematic review. (9th June 2022) - Li, Caili; Xu, Xiaofeng; He, Lingxiao; Zhang, Mingming; Li, Jing; Jiang, Yan
Abstract: Aim: The purpose of this review was to evaluate the content, validity and reliability of patient‐reported questionnaires on patient participation in patient safety. Background: Patient participation in patient safety is one of the key strategies that are increasingly regarded as a critical intervention to improve the quality of safety care. Evaluation: A systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. The content, reliability and validity of patient‐reported questionnaires on patient participation in patient safety were assessed. Key issues: Twenty‐seven studies were included for data extraction and synthesis. The questionnaire contents most commonly used to describe patient participation in patient safety were 'attitudes and perceptions', 'experience', 'information and feedback' and 'willingness'. Internal consistency was evaluated for 17 questionnaires, and test–retest reliability was tested for four questionnaires. Content validity was assessed among all included questionnaires, and structural validity was evaluated for 12 questionnaires. Conclusions: Future research targeting the different safety issues is still indispensable for developing patient‐reported questionnaires with great psychometric quality in validity, reliability, feasibility and usability in patient participation in patient safety. Implications for Nursing Management: Clinical nurses should consider the internal consistency, test–retest reliability, content validity and structural validity of the questionnaires that have been positively appraised for methodological quality before use.